Implementasi Penggunaan Teknoligi Dalam Produk Bank Syariah Indonesia di Era Generasi Anak Muda Di Bank Syariah Indonesia KCP Medan Simpang Limun - Erlina Erlina; Ahmad Perdana Indra (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The aim of this research is for us to find out how influential Bank Syariah Indonesia's products are in the era of the generation of children who choose to save at Bank Syariah Indonesia, which we researched precisely at KCP Medan Simpang Limun. The research we took was taken from the results of a survey where in the era of the younger generation how many people used Bank Syariah Indonesia to access their finances. Data collection will be collected through interviews or through data from the opening of a savings book at Bank BSI KCP Medan Simpang Limun. The results of the implementation research into the use of Bank Syariah Indonesia products in the era of the younger generation will be completed through data from Bank Syariah Indonesia KCP Medan Simpang Limun where the results of implementation will be proven how influential the young generation is in using access to Indonesian sharia banking at this time at KCP Medan Simpang Limun.